Optical mode switch based on multimode interference couplers. (29th December 2016) - Xiao, Huifu; Deng, Lin; Zhao, Guolin; Liu, Zilong; Meng, Yinghao; Guo, Xiaonan; Liu, Guipeng; Liu, Su; Ding, Jianfeng; Tian, Yonghui
Abstract: In this paper, we propose an optical mode switch based on two cascaded multimode interference (MMI) couplers. After a fundamental mode divided into two equal-power fundamental modes in the first MMI coupler, the thermo-optic effect is employed to modulate the phase of the two fundamental modes before directed to the next MMI for the purpose of mode switching. By adjusting the electric signals applied to the modulation arms, the proposed device can implement mode switching in three states: (a) one first-order and two fundamental modes simultaneously output, (b) one first-order mode output, and (c) two fundamental modes output. As a result, the simulated excess losses are −0.29 dB, −0.10 dB, and −0.63 dB, respectively.